ThermoTargetMiner - Lyu, Hezheng (SciLifeLab Serve, 2026)
ThermoTargetMiner is an interactive Shiny application that enables simplified visualization and exploration of drug–target relationships derived from the Proteome Integral Solubility Alteration (PISA) assay. The app integrates processed data from 67 approved drugs and candidate compounds tested in lung cancer cell lines, providing users with tools to: · Visualize proteome-wide solubility shifts in lysate and living lung cancer cells. · Identify and compare targets across different drugs and conditions. · Retrieve a structured list of discovered targets for each compound. By combining intuitive data handling with accessible visualization, ThermoTargetMiner serves as a practical resource for researchers interested in drug target discovery and mechanism-of-action studies in lung cancer.